Games and information : an introduction to game theory - Rasmusen, Eric (Blackwell, 2001)
"Written in a crisp and approachable style, Games and Information: An Introduction to Game Theory uses simple modelling techniques and straightforward explanations to provide students with an understanding of game theory and information economics. The third edition brings the text totally up-to-date. New topics include price discrimination, mechanism design, and value uncertainty in auctions. Other chapters have been extensively reorganized or rewritten.".